A review on drivers and barriers towards sustainable supply chain practices - Mee, Yean Tay; Abd Rahman, Azmawani; Abdul Aziz, Yuhanis; Sidek, Shafie (International Association of Computer Science and Information Technology Press, 2015)
The rising environmental concerns are encouraging consumers to have greater awareness of their purchase decisions. Firms are implementing measures geared to offering green substitutes for traditional products and services. However, the effort towards sustainable supply chain management (SSCM) is not as straightforward since organization would face obstacles. The aim of this paper is to identify the barriers and drivers towards the implementation of the sustainable supply chain management (SSCM). Through the review of the literature, it was found that there are various factors that have been documented to influence an organization in making the decision towards SSCM implementation.